Makna Verbal Dalil Moro dan Implikasi Terhadap Masyarakat Ternate (Tinjauan Semantik) - Nurmina Lakarai; Sulami Sibua (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted with the aim of knowing how the verbal meaning of the proposition of Moro in Ternate society, what is the implication of the proposition of Moro for the community of Ternate. The method used in this research is descriptive qualitative, and the instruments used are observation, interview, documentation, free-to-speak (SBLC), and SPEAKING. Based on the results of the analysis of the Verbal Meaning of Moro's Dalil and Implications for the Ternate Society, it can be seen that the Moro argument is the advice of previous parents in the Ternate language which contains exemplary advice and becomes a life guide for every human being, as a medium in traditional ceremonies, as competitions in arts and cultural events, as the preservation of regional languages, and to strengthen friendship. Many people of Pulau Hiri Subdistrict still use the values ​​of Moro theorem in their daily life, especially among their parents. There are also young people who understand and are able to explain Moro's argument, especially among students. The solution is that apart from teaching parents to their children, the local government also needs to pay attention to provide a forum that can preserve Moro arguments in the sub-district of Hiri Island.